-(2n-5n)+n=3n-7

Simple and best practice solution for -(2n-5n)+n=3n-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(2n-5n)+n=3n-7 equation:


Simplifying
-1(2n + -5n) + n = 3n + -7

Combine like terms: 2n + -5n = -3n
-1(-3n) + n = 3n + -7

Remove parenthesis around (-3n)
-1 * -3n + n = 3n + -7

Multiply -1 * -3
3n + n = 3n + -7

Combine like terms: 3n + n = 4n
4n = 3n + -7

Reorder the terms:
4n = -7 + 3n

Solving
4n = -7 + 3n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-3n' to each side of the equation.
4n + -3n = -7 + 3n + -3n

Combine like terms: 4n + -3n = 1n
1n = -7 + 3n + -3n

Combine like terms: 3n + -3n = 0
1n = -7 + 0
1n = -7

Divide each side by '1'.
n = -7

Simplifying
n = -7

See similar equations:

| y/8-6=2 | | Y=x^2-2x-26 | | 0.70x+0.25(210-x)=0.50(100) | | 6y+4-2y=32-3y | | 6(-4m+5)=-114 | | 4(4x-2)=50 | | 3x+6y=24forx | | 10x+4x+12=360 | | 7x-5=2x+17 | | 3(y-1)-(y+2)=7 | | x-3+4=-6 | | Y=-5k^2+65k-150 | | 5y^2-1+2(y^2+2)= | | 3x+9=-63-9 | | 3-7(-6p+3)=-p+9 | | -(2y+1)=8(y+2)+2 | | 0.70x+0.30(360-x)=0.60(100) | | 4z+6.1= | | 0.2d-1.2=0.4d+2 | | 5x-2x+9=45-9x | | 4cos^2(x)+8cos(x)-5=0 | | 4+10h=8h+12 | | 18x+-1(8x+-7)=67 | | 188x-(8x-7)=67 | | sin(45-x)=0 | | 2x+X+2x+x=180 | | 2Y+3=6Y-7 | | Y=a^2-8a+15 | | 0.35x+0.40(4)=0.39(x+4) | | 2(x-5)=(5-x) | | 2x^4-x^2-216=0 | | -4(k+3)=6-2k |

Equations solver categories